The Influence of Think, Talk and Write (TTW) Learning Model on The Ability to Write Description and Learning Motivation of Fifth Grader - Irawati Amir; Munirah Munirah; Erwin Akib (Universitas Muhammadiyah Enrekang, 2022)
This research is an experimental study with a design that aims to see the effect of implementing the Think, Talk, and Write (TTW) learning model on the ability to write descriptions and learning motivation of class V Cluster III students, Kahu District, Bone Regency. The population in this study were all students of class V, Group III, Kahu District, Bone Regency. Then two schools were chosen randomly as the research sample. SD Inpres 12/79 Hulo and SD Inpres 5/81 Tompon Patu with 28 students. Data was collected through test, questionnaire, and observation techniques. The collected data were analyzed through descriptive statistical analysis and inferential statistical analysis. The results showed that (1) the students' writing ability at the posttest stage of the experimental class had an average score in the good category while the control class was in the sufficient category; (2) students' learning motivation in the experimental class is in the high category; (3) based on hypothesis testing, the application of the TTW learning model affects the description writing skills and students' learning motivation. So it can be concluded that the Think, Talk, and Write (TTW) learning model has an effect on the description writing skills and learning motivation of the fifth grade students of Cluster III, Kahu District, Bone Regency.